Announcement: National Annual Award for Medical Humanities - 2025 - Dhaliwal, Upreet (Research and Humanities in Medical Education, 2024)
Objective: To recognize and honor persons for promoting Subjects of Humanities in Medical Education & Practice Patron Founder Late Dr Sunil Pandya, Ex-Professor & Head, Dept. of Neurosurgery, GS Medical College & KEM Hospital, Parel, Mumbai Chairperson Dr. Ravi Ramakantan, Ex-Professor & Head, Dept. of Radiodiagnosis, GS Medical College & KEM Hospital, Parel, Mumbai Initiator Dr. Apoorva Pauranik, Emeritus Professor of Medicine (MGM Medical College & MY Hospital, Indore)